Development of physical employment standards of specialist paramedic roles in the National Ambulance Resilience Unit (Naru). (September 2021) - Siddall, Andrew G.; Rayson, Mark P.; Walker, Ella F.; Doherty, Julianne; Osofa, Josh I.; Flood, Tessa R.; Hale, Beverley; Myers, Steve D.; Blacker, Sam D.
Abstract: Aim: To develop evidence-based role-specific physical employment standards and tests for National Ambulance Resilience Unit (NARU) specialist paramedics. Methods: Sixty-two (53 men, 9 women) paramedics performed an array of (1) realistic reconstructions of critical job-tasks (criterion job performance); (2) simplified, easily-replicable simulations of those reconstructions and; (3) fitness tests that are portable and/or practicable to administer with limited resources or specialist equipment. Pearson's correlations and ordinary least products regression were used to assess relationships between tasks and tests. Performance on reconstructions, subject-matter expert and participant ratings were combined to derive minimum acceptable job performance levels, which were used to determine cut-scores on appropriate correlated simulations and tests. Results: The majority of performance times were highly correlated with their respective simulations (range of r: 0.73–0.90), with the exception of those replicating water rescue (r range: 0.28–0.47). Regression compatibility intervals provided three cut-scores for each job-task on an appropriate simulation and fitness test. Conclusion: This study provides a varied and easily-implementable physical capability assessment for NARU personnel, empirically linked to job performance, with flexible options depending on organisational requirements. Highlights: Specialist paramedics require evidence-based physical standards and tests for role. We designed complex realistic scenarios to measure criterion job performance. Field-expedient gym tests and job simulations predicted criterion performance. We combined objective and subjective data to define acceptable performance. Regression uncertainty intervals provided flexible employment standards.